Experimental evidence for a dynamical crossover in liquid aluminium. (14th October 2015) - Demmel, F; Fraile, A; Szubrin, D; Pilgrim, W-C; Morkel, C
Abstract: The temperature dependence of the dynamic structure factor at next-neighbour distances has been investigated for liquid aluminium. This correlation function is a sensitive parameter for changes in the local environment and its Fourier transform was measured in a coherent inelastic neutron scattering experiment. The zero frequency amplitude decreases in a nonlinear way and indicates a change in dynamics around . From that amplitude a generalized viscosity can be derived which is a measure of local stress correlations on next-neighbour distances. The derived generalized longitudinal viscosity shows a changing slope at the same temperature range. At this temperature the freezing out of degrees of freedom for structural relaxation upon cooling sets in which can be understood as a precursor towards the solid state. That crossover in dynamics of liquid aluminium shows the same signatures as previously observed in liquid rubidium and lead, indicating an universal character.